Investigation of the effects of managed ice field characteristics on a dynamic positioning AHTS vessel using physical modelling techniques. (15th February 2022) - Islam, Mohammed; Lau, Michael; Brown, Jeffery; Gash, Robert; Pearson, Wayne; Mills, Jason
Abstract: This paper presents the tools, techniques and outcomes of a model testing program of a dynamically positioned (DP) Ice-1A classed Anchor Handling Tug Supply (AHTS) vessel called the "Magne Viking" in different managed ice environments with ice thickness, concentration, floe size, floe distribution, drift speed, and ice encroachment direction as test variables. A total of 168 test runs were carried out in 7 ice sheets to evaluate the vessel's thruster forces and moment on the horizontal plane and the vessel's 6-DOF motions and accelerations. The time series and probability of exceedance plots of thruster forces and yawing moments are presented, along with the vessel's positioning relative to a set-point in various managed ice conditions. In addition, investigations are carried out to evaluate the influence of various ice field parameters on the time-averaged and time-dependent thruster forces and moment. Both measurements and video recordings confirmed complex and stochastic ice-ship-basin wall interactions and different ice failure modes. Overall, the study demonstrated the capability of the DP-controlled ship to maintain the station for most head-on tests and the oblique ice tests not exceeding 15°. The dataset and video recordings acquired through the testing have improved the understanding of the dynamic ice-vessel interactions. Highlights: A physical modelling of a DP-controlled Ice-1A classed Anchor Handling Tug Supply vessel, Magne Viking, was completed. Evaluated the vessel responses in varied ice concentration, thickness, floe size, strength, and drift speed & direction. The DP-controller was capable in maintaining the station for most head-on tests and the oblique tests with heading < 10°. Analysis indicated that the thruster forces primarily increased with concentration, thickness, floe size, and drift speed. The large dataset and video recordings helped to evaluate and improve understanding of the dynamic ice-vessel interactions. The dataset provided sufficient information for developing novel ice force models for real-time applications.